Low Complexity RCP-OTFS Systems with Fractional Doppler Shifts - Kara, Hilseyin Samet; Serbes, Ahmet; Hokelek, Ibrahim; Gorcin, Ali (IEEE, 2024)
Doppler resistant orthogonal time-frequency-space (OTFS) modulation has gained attention to be implemented for next-generation wireless communications systems. Various OTFS frame structures, including the reduced cyclic prefix (RCP), are utilized in OTFS systems with rectangular pulse shaping waveform. In this paper, the input-output relationship of the RCP-OTFS modulation scheme is formulated in the delay-time (DT) domain instead of the conventional delay-Doppler (DD) domain. A realistic system model is considered by expressing the Doppler shifts fractionally in the equations. Simulation results indicate RCP-OTFS calculations in the DT domain yields exactly the same result as the relationship calculated in the DD domain. Furthermore, the theoretical and simulation results confirm that the computational complexity of the proposed approach is considerably lower than that of the conventional RCP-OTFS method.
Keywords: OTFS; delay-Doppler domain; delay-time domain; fractional Doppler shift; Computer Science; Engineering; Telecommunications